Description of Tradescantia schwirkowskiana (Commelinaceae), a narrow endemic new species from Santa Catarina, southern Brazil, and typification of T. crassula - Funez, Luís Adriano; Hassemer, Gustavo; Ferreira, João Paulo Ramos (Phytotaxa, 2016)
This contribution presents and describes Tradescantia schwirkowskiana, a narrow endemic new species from Santa Catarina state, southern Brazil. We assess here the conservation status of this new species as critically endangered, according to the IUCN criteria. We present here a complete description, illustrations and comments on the new species, along with an identification key to the species of Tradescantia that occur in Santa Catarina. Furthermore, we designate here a lectotype and an epitype for T. crassula, the morphologically-closest species to T. schwirkowskiana.